Analysis of Factors Influencing Life Expectancy in Developing Countries in India - Patel, Sanjay (Journal of Statistics and Actuarial Research, 2024)
Purpose: The aim of the study was to analyze the analysis of factors influencing life expectancy in developing countries Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Factors influencing life expectancy in developing countries include healthcare access, nutrition, sanitation, economic stability, education, and governance. Access to healthcare and quality services, along with adequate nutrition and sanitation, significantly impact life expectancy. Economic stability facilitates healthcare investments, while education and stable governance influence health behaviors and service availability, contributing to longer life spans in these regions. Unique Contribution to Theory, Practice and Policy: Social determinants of health theory, economic growth theory & epidemiological transition theory may be used to anchor future studies on factors influencing life expectancy in developing countries. Evaluate the effectiveness of existing health interventions and policies in improving life expectancy. Advocate for integrated policies that address the social determinants of health, including education, income inequality, housing conditions, and access to clean water and sanitation.